Diminishing Marginal Utility and the Teaching of Economics: A Note - TODOROVA, Tamara (Journal of Research in Educational Sciences; Vol 12 No 14 (2021): JRES, Volume XII, Issue 14, 2021DO - 10.14505/jres.v12.14.02, 2021)
This paper discusses how utility can be taught in undergraduate courses in microeconomics so that to illustrate total and marginal utility, the law of diminishing marginal utility, and consumer rationality. Diminishing marginal utility is essential in describing rational consumer behavior, overconsumption, and oversaturation to students of economics. We demonstrate a quadratic and a logarithmic total utility with the subsequent forms and shapes of marginal utility. From what it seems there is no contradiction between diminishing marginal utility in the univariate context of consuming one good and the indifference curve as the multivariate case of two goods consumed.